Baseline anemia in patients undergoing percutaneous coronary intervention after an acute coronary syndrome—A paradox of high bleeding risk, high ischemic risk, and complex coronary disease. (13th July 2017) - Yazji, Khaled; Abdul, Fairoz; Elangovan, Senthil; Ul Haq, Muhammad Z.; Ossei‐Gerning, Nick; Morris, Keith; Anderson, Richard; Kinnaird, Tim
Abstract : Objectives: To define more clearly the associations between baseline anemia, bleeding/ischemia risk, coronary disease severity, and outcomes by revascularization completeness. Background: Anemia is associated with adverse outcomes in patients presenting with an acute coronary syndrome (ACS). Methods and Results: Data was sourced from hospital databases for patients admitted with an ACS to a single center between 2011 and 2014. Using WHO anemia criteria, 468 (26.9%) of 1731 patients were anemic. In anemic patients, the mean CRUSADE score (34.6 ± 16.9 vs 24.6 ± 13.4, P < 0.0001), mean GRACE scores (165.8 ± 44.9 vs 141.6 ± 40.1, P < 0.0001), and percentage of patients with a high/very high CRUSADE score combined with a high GRACE score (69.3 vs 48.3%, P < 0.0001) was much greater than non‐anemic patients. Patients with baseline anemia were more likely to have left main or chronic occlusive disease, and more diseased vessels. The percentage of patients with residual disease (41.2 vs 30.7%, P < 0.0001), the number of residual diseased vessels (0.59 ± 0.83 vs 0.42 ± 0.72, P < 0.0001), and the percentage with a residual CTO (62.4 vs 56.4%, P = 0.036) were all higher than in non‐anemic patients. The duration of anti‐platelet therapy was significantly shorter in anemic patients (7.8 ± 4.3 vs 11.2 ± 2.4 months, P < 0.001). At 12‐months, mortality and stent thrombosis were more likely to occur in anemic patients, with the number of residual vessels associated with adverse survival regardless of anemia status. Conclusions: Patients with anemia present with high ischemia and bleed risk scores, complex coronary disease, and have adverse outcomes. Incomplete revascularization was associated with worse survival regardless of anemia status.